Estimating the Sequestration Potential of Organic Carbon in Forest Soils in the Central Middle Atlas: A Tool to Fight Climate Change (Atlas Journal of Biology, 2019)
Soil organic carbon sequestration is an important matter in international negotiations to fight climate change through a reduction in greenhouse gas (GHG) emissions. This study was carried out in the forests of the Moroccan Central Middle Atlas, with the objective of determining the storage of carbon in the high organo-mineral layer of soils (<30 cm deep) and under different spontaneous forest species in this area. It shows that the soil organic carbon stock (SCOS) in these forest ecosystems is higher in green oak and deciduous zeen oak forest stands, recording 264.73 and 251.54 t/ha respectively on a basaltic substrate followed by cedar (resinous species) (178.07 t/ha). Mixed forest stands come at last with low SCOS (109.02 t/ha). This variation may be attributed to several factors, mainly the type of vegetation, the physical and chemical soil properties and soil type of the studied area.